A cidade de Salvador e a mídia externa: beleza roubada? - Goncalves, Dirlene Guimarães de Barros (2008)
The city of Salvador in Bahia state, as well as major cities, is experiencing changes related to the dynamics of globalization that emphasizes consumption habits which are broadcast by the capitalist system. The growth of investment in the market for outdoor advertising contributes to the increase in external media elements of the urban landscape. This paper shows the performance of the external media, specifically the billboard, light front panel and gable, with the various ways of using these elements in the urban environment, questioning its interference as a key generator visual pollution, in view of the article published on the website SESCSP entitled Stealing Beauty, which said that advertising is classified as a polluter of the urban environment, contributing to a blockage of the visual field and interfering in the trial of the beauty of the city. In the literature review, authors dealing with the phenomena and urban issues, beauty and the media in the modern city were discussed. News were collected from building on the controversy generated about the visual pollution from the approval of the Clean City Project of São Paulo, about the process of growth of the external media in the city of Salvador and the role of supervision by the government on the implementation of a master plan. The analysis shows that the external media is present in the contemporary cities and aims at predominantly marketing purposes.